Evaluation of the body composition, blood lipids and health life-style in employment and unemployment women - Arslan, Cengiz; Savucu, Yuksel; Ceviz, Deniz (Drunpp-Sarajevo, 2011)
Aim: The aim of the study was to establish the effects on blood lipids, body compositions and healthy lifestyle behaviors of unemployed and employed women. Method: 797 subjects were participated to this study (HW: 383, 42.60+/-8.65; EW: 414, 41.83+/-6.31 years). Life style behavior was questioned by using HPLP-II scale of Walker&Pender. Body composition was measured by bioelectric impedance (BIA) analysis method. Blood lipids and blood pressure were measured by using standard methods. Results: There was found significant difference weight, body mass index (BMI), waist-to-hip ratio (WHR), waist circumference (WC), age matched of body (AMB), percent of body fat and mass of body fat (MBF) in EW. Soft lean mass (SLM) and total body water (TBW) were observed difference in HW (p<0.001). No significant difference was found in spiritual growth, interpersonal relations and stress management from HPLP-II scales, (p>0.05). A significant difference was found for health responsibility, exercise and nutritional habits and HPLP-II score in EW (p<0.05). HDL, LDL, TG, T-Cholesterol and glucose values were observed in moderate levels. Number of children of HW and EW was found as 3.0+/-08 and 2.0+/-0.80 (respectively), (p<0.001). Conclusion: HPLP-II means score was found higher in EW. As body type of HW and EW included in overweight class. The increase in the number of children determined the rise to advantage obesity in body type. Regular diet habits and educational level were observed to be important factor in the control of weight body.
Keywords: Women; body composition; obesity; blood lipids; health lifestyle